Pengaruh Perumbuhan Ekonomi, Tingkat Pengangguran Terbuka (TPT), Tingkat Partisipasi Angkatan Kerja (TPAK), dan Rata- Rata Lama Sekolah (RLS) terhadap Indeks Pembangunan Manusia (IPM) di Kabupaten Gresik Tahun 2004-2023 - Siti Asmaul Faujiah; Debby Nindya Istiandari (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of economic growth, the open unemployment rate, the labor force participation rate, and the average years of schooling on the Human Development Index in Gresik Regency from 2004 to 2023. Secondary data obtained from the Central Statistics Agency (BPS) were analyzed using multiple linear regression with SPSS. The results indicate that, partially, the average years of schooling and the labor force participation rate have a positive and significant effect on the Human Development Index. In contrast, economic growth and the open unemployment rate do not show a significant effect. However, simultaneously, all four independent variables significantly influence the Human Development Index. This indicates the importance of investing in education and increasing productive labor force participation in sustainable human development efforts. Based on this, it is recommended that the Gresik Regency government prioritize policies that support improving the quality of education, job training, and creating quality jobs. Furthermore, cross-sector collaboration is needed to ensure that economic growth directly impacts community welfare by reducing unemployment and increasing human resource capacity.